2019
DOI: 10.3390/ijtpp4040040
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of Brush Seals by Oil and Salt and Its Impact on Rubbing and Hysteresis Behaviour

Abstract: The literature already contains some experimental, analytical and numerical investigations on the rubbing and hysteresis behaviour of brush seals. What the investigations have in common is that they were carried out with new and uncontaminated seals, or that such a condition was assumed. The influence of contamination has not been explicitly investigated yet. Particularly in stationary gas and steam turbines, foreign substances can accumulate on and in the bristle package during steady-state operation. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The work by Pfefferle [13] was continued at the ITS in the subsequent years on a modified test rig (see Refs. [17][18][19][20]). The experimental investigations that were presented in these publications with subsequent calculation of the rotor heat input using an FE model demonstrated the influence of the geometry and operating parameters, as well as the degree of contamination of the bristle package on the heat flux distribution.…”
Section: Heat Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…The work by Pfefferle [13] was continued at the ITS in the subsequent years on a modified test rig (see Refs. [17][18][19][20]). The experimental investigations that were presented in these publications with subsequent calculation of the rotor heat input using an FE model demonstrated the influence of the geometry and operating parameters, as well as the degree of contamination of the bristle package on the heat flux distribution.…”
Section: Heat Transfermentioning
confidence: 99%
“…The recalculation of the experimental tests by means of the FE analyses (see Refs. [17][18][19]) has shown that the areas further inwards are only slightly thermally affected within the rubbing period of 30 s. At the inlet, the total pressure and temperature are set according to the respective measured values from the experiments. At the outlets, the static pressures and temperatures are specified.…”
Section: Description Of the Modelmentioning
confidence: 99%
“…Li et al (2012) analyzed effect of clearance sizes on the leakage performance of a labyrinthbrush seal and found that the blow-down effect should be considered for clearance brush seals. Hildebrandt et al (2019) experimentally investigated the effect of bristle pack density, rotor-bristle interference, rotational speed and pressure difference on leakage flow of a kind of clamped brush seal with an axially inclined bristles pack.…”
Section: Introductionmentioning
confidence: 99%